PENGGUNAAN AIR KELAPA UNTUK MENINGKATKAN PERKECAMBAHAN DAN PERTUMBUHAN PALEM PUTRI (VEITCHIA MERILUI) - Sujarwati '; Siti Fathonah; Elna Johani; Herlina ' (Universitas Riau, 2011)
The present study was aimed to Ttnd out the most effective concentration of coconut water on the seedgermination and seedling growth of Veitchia merillii. The study used two experiments: seed germination andseedling growth. The study used Completely Randomized Design with live coconut water concentrations: 0%(K„). 25% (K,), 50% (K,